Mechanical evaluation of quad-helix appliance made of low-nickel stainless steel wire - Rogério Lacerda dos Santos; Matheus Melo Pithon (Dental Press Editora, 2013)
OBJECTIVE: The objective of this study was to test the hypothesis that there is no difference between stainless steel and low-nickel stainless steel wires as regards mechanical behavior. Force, resilience, and elastic modulus produced by Quad-helix appliances made of 0.032-inch and 0.036-inch wires were evaluated. METHODS: Sixty Quad-helix appliances were made, thirty for each type of alloy, being fifteen for each wire thickness, 0.032-in and 0.036-in. All the archwires were submitted to mechanical compression test using an EMIC DL-10000 machine simulating activations of 4, 6, 9, and 12 mm. Analysis of variance (ANOVA) with multiple comparisons and Tukey's test were used (p < 0.05) to assess force, resilience, and elastic modulus. RESULTS: Statistically significant difference in the forces generated, resilience and elastic modulus were found between the 0.032-in 0.036-in thicknesses (p < 0.05). CONCLUSIONS: Appliances made of low-nickel stainless steel alloy had force, resilience, and elastic modulus similar to those made of stainless steel alloy.